Some problems of the linear theory of systems of ordinary differential equations - Samoilenko, A.M. (Український математичний журнал, 2011)
We consider problems of the linear theory of systems of ordinary differential equations related to the investigation of invariant hyperplanes of these systems, the notion of equivalence for these systems, and the Floquet – Lyapunov theory for periodic systems of linear equations. In particular, we introduce the notion of equivalence of systems of linear differential equations of different orders, propose a new formula of the Floquet form for periodic systems, and present the application of this formula to the introduction of amplitude-phase coordinates in a neighborhood of a periodic trajectory of a dynamical system. Розглянуто проблеми лiнiйної теорiї систем звичайних диференцiальних рiвнянь, пов’язанi з дослiдженням iнварiантних гiперплощин таких систем, поняттям еквiвалентностi для вказаних систем та теорiєю Флоке – Ляпунова для перiодичних систем лiнiйних рiвнянь. Зокрема, введено поняття еквiвалентностi систем лiнiйних диференцiальних рiвнянь рiзних порядкiв, запропоновано нову формулу вигляду Флоке для перiодичних систем, наведено застосування цiєї формули для введення амплiтудно-фазових координат в околi перiодичної траєкторiї динамiчної системи.